L-Buthionine sulfoximine detection and quantification in polyurea dendrimer nanoformulations - Mota, Pedro (2019)
l-Buthionine sulfoximine (l-BSO) is an adjuvant drug that is reported to increase the sensitivity of cancer cells to neoplastic agents. Dendrimers are exceptional drug delivery systems and l-BSO nanoformulations are envisaged as potential chemotherapeutics. The absorption of l-BSO at a low wavelength limits its detection by conventional analytical tools. A simple and sensitive method for l-BSO detection and quantification is now reported. In this study, l-BSO was encapsulated in a folate-targeted generation four polyurea dendrimer (PUREG4-FA2) and its release profile was followed for 24 h at pH 7.4 and 37 ◦C. The protocol uses in situ l-BSO derivatization, by the formation of a catechol-derived orto-quinone, followed by visible detection of the derivative at 503 nm. The structure of the studied l-BSO derivative was assessed by NMR spectroscopy.